Mechanical joining of high-strength multi-material systems − trends and innovations☆ - Merklein Marion; Jäckisch Manuel; Kuball Clara-Maria; Römisch David; Wiesenmayer Sebastian; Wituschek Simon (Mechanics & Industry, 2023)
In conjunction with mechanical joining processes. Mechanical joining processes play a key role for the realization of multi-material lightweight structures, which are essential with regard to environmental protection. However, joining of dissimilar high-strength materials is challenging due to the varying properties of the joining partners and due to their high flow stresses and often limited ductility. Thus, the evolution of established processes as well as the development of innovative and highly productive joining technologies are necessary. Requirements for a highly volatile production environment are versatility, flexibility, resilience and robustness. Within this contribution, current trends and innovations related to selected mechanical joining processes for enabling the material mix are outlined in order to point out opportunities to address these requirements in the future. In this context, joining using cold formed pin structures is presented as a promising approach for connecting dissimilar materials like metals to fibre-reinforced plastics. Furthermore, it is shown how the shear-clinching technology can be combined with a process-adapted application of locally limited heat treatment in order to promote the joinability and control the material flow during joining. A novel approach for reducing process forces and expanding process windows is the use of ultrasonic assistance for mechanical joining operations, which is demonstrated by the example of a nut staking process with superimposed high frequency oscillation. As concerns the widely used self-piercing riveting technique, current research activities relate not only to the further development of the joining process itself, for example by combining self-piercing riveting and tumbling, but also to the use of new rivet materials like high strain hardening stainless steels. In addition, the evolution towards mechanical joining 4.0 against the background of data-based process control in conjunction with of mechanical joining processes is also subject of the considerations.